Integrasi Pendidikan Kewirausahaan: Strategi Eksplorasi Karir Mahasiswa Universitas Baiturrahmah - Sari, Sefni Novita; Rahmi, Yuri; Siregar, Eva Anzani; Evanita, Susi; Armiati, Armiati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The university as an educational institution has an important role to play in preparing the younger generation to become successful entrepreneurs. The study aims to analyze the integration of entrepreneurial education into the career exploration strategy of Baiturrahmah University students. The research uses qualitative descriptive methods with data collection techniques through interviews. The research informant is an entrepreneurship lecturer and a student at Baiturrahmah University. The research shows that Baiturrahmah University has implemented a variety of entrepreneurial education integration strategies and such strategies have had a positive impact on students in exploring their careers including improving their understanding of the world of work and entrepreneurship opportunities, developing the skills and knowledge needed, boosting confidence and building networks and connections. Recommendations for the integration of entrepreneurship education at Baiturrahmah University can be more effective in helping students to their career goals and contribute to the development of enterprise in Indonesia.